Biological targeted therapy for type 2 inflammation bronchial asthma - ZHANG Mingqiang, MU Xiangdong (Xin yixue)
Bronchial asthma is a chronic inflammatory disease of the airway involving multiple inflammatory cells and cytokines. Severe asthma is characterized by recurrent attacks and persistent symptoms such as coughing， chest tightness， shortness of breath， and wheezing， etc.， which are difficult to be alleviated and have a significant impact on the quality of life of patients. At present， the standard therapy of combining high-dose inhaled corticosteroids and long-acting bronchodilators is recommended， but asthma symptoms of certain patients cannot be fully controlled， which is primarily related to persistent type 2 inflammation. For severe asthma patients with persistent type 2 inflammation， biological targeted drugs can be chosen. Biological targeted therapy can significantly mitigate symptoms， reduce the frequency of acute exacerbations and oral use of corticosteroids， bringing new hope to asthma patients with severe type 2 inflammation. This article reviews the research progress in biological targeted therapy for type 2 inflammation in patients with bronchial asthma.